Fade margin analysis due to duststorm based on visibility data measured in a desert - Islam, Md. Rafiqul; Elshaikh, Zain Elabdin Omer; Khalifa, Othman Omran; Alam, A. H. M. Zahirul; Khan, Sheroz (Science Publications, 2010)
Problem statement: The fade margin analysis of microwave propagation in areas affected by duststorm had been presented in this study. Approach: Based on long term duststorm data recorded in Riyadh-Saudi Arabia, the fade margin due to duststorm effects estimated. Results: The fade margin due to duststorm then derived under various water contents during the storm. Conclusion/Recommendations: It was particularly shown that duststorm have comparable effects on link reliability for typical storms.